2008
DOI: 10.1016/j.electacta.2007.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Electrosynthesis and electrochemical characterisation of phenazine polymers for application in biosensors

Abstract: A comparative investigation has been undertaken of the electrosynthesis and electrochemical properties of three different electroactive polymers on carbon film electrode substrates: poly(neutral red) from the phenazine dye neutral red, and poly(methylene green) and poly(methylene blue), from the corresponding phenothiazine dyes. The formation of the radical cation at different potentials and the chemical structures of the monomers both influence the electropolymerisation process of the three polyaromatic dyes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
63
1
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(78 citation statements)
references
References 33 publications
8
63
1
4
Order By: Relevance
“…After electropolymerization, an adherent polymer observed on the GCE. The similar results were obtained in the electrochemical polymerization of methylene blue and methylene green [52]. Karyakin et al [53] reported that the polymerization of monomer containing one or two tertiary amine groups was taking place through tertiary amine.…”
Section: Modification Of Electrode Surfacesupporting
confidence: 71%
See 1 more Smart Citation
“…After electropolymerization, an adherent polymer observed on the GCE. The similar results were obtained in the electrochemical polymerization of methylene blue and methylene green [52]. Karyakin et al [53] reported that the polymerization of monomer containing one or two tertiary amine groups was taking place through tertiary amine.…”
Section: Modification Of Electrode Surfacesupporting
confidence: 71%
“…Moreover, as polymerization occurs, more tertiary amine groups become nitrogen bridges and these bridges become electroactive similar to those in polyaniline and poly(thionine) films [54,55]. PyB monomers were able to form an electroactive polymer by anodic oxidation from acidic aqueous solutions similar to poly(methylene blue) nor poly(methylene green) since its chemical structure resembles with methylene blue and methylene green [10,52,53]. The structure of poly(PyB) film might similar to the hypothetical structure proposed for poly(methylene blue).…”
Section: Modification Of Electrode Surfacementioning
confidence: 99%
“…The behaviour is similar to that observed for PNR/CFE [33]. In order to elucidate whether some fragments of oligomers of the two polymers are present on the electrode surface, an experiment was performed by dipping the modified electrodes in buffer overnight.…”
Section: Pedot/pnr Characterisationmentioning
confidence: 93%
“…A síntese de polímeros condutores pode ser realizada por meio da oxidação ou redução química ou eletroquímica de uma substância e podem apresentar a condutividade elétrica de um metal [5,42]. Assim, a escolha do método de síntese é importante uma vez que influencia na qualidade e propriedades finais do polímero.…”
Section: Polímeros Condutoresunclassified
“…Em particular, a modificação da superfície de eletrodos por eletropolimerização de várias fenazinas, fenoxazinas e fenotiazinas foram relatadas na literatura [42,43,[47][48][49].…”
Section: Eletropolimerizaçãounclassified